Remote monitoring and teleconsultations can reduce greenhouse gas emissions while maintaining quality of care in cystic fibrosis - Martinus C. Oppelaar; Michiel A. G. E. Bannier; Monique H. E. Reijers; Hester van der Vaart; Renske van der Meer; Josje Altenburg; Lennart Conemans; Lennart Conemans; Bart L. Rottier; Bart L. Rottier; Marianne Nuijsink; Lara S. van den Wijngaart; et al. (Frontiers Media S.A., 2024)
BackgroundRemote care usefulness and climate change co-benefits should be addressed simultaneously to incentivize political action.ObjectivesTo assess the changes in healthcare consumption, lung function and greenhouse gas (GHG) emissions during the COVID-19 pandemic in Dutch cystic fibrosis (CF) care.DesignRetrospective multicentre observational study in five Dutch CF centres.MethodsEighty-one participants were included. Healthcare consumption was described alongside the COVID-19 Stringency Index (2019-2022). Travel related GHG emissions were calculated for every clinic visit. Changes in percentage predicted Forced Expiratory Volume in one second (ppFEV1) were assessed using a paired-samples T-test.ResultsHealthcare consumption patterns followed COVID-19 public health measure stringency but returned back to the "old normal". Emission of 5.450, 3 kg of carbon dioxide equivalents were avoided while quality of care was relatively preserved. ppFEV1 declined as expected (ΔMeans 3.69%, 95%CI 2.11-5.28).ConclusionRemote monitoring of lung function and symptoms and teleconsultations in CF can reduce GHG emissions while maintaining quality of care. As health sectors constitute a large share of national climate change footprints, digital health can partly alleviate this burden by reducing private travel.